Serum PTH is not a good marker for defining a threshold for vitamin D deficiency - Jorde, Rolf; Grimnes, Guri (Endocrine Connections, 2020)
Objective : In addition to its skeletal effects, vitamin D may also be important for health in general. It is uncertain what level of serum 25-hydroxyvitamin D (25(OH)D), marker of vitamin D status, is sufficient for these effects. With decreasing serum 25(OH)D levels there is an increase in serum PTH. The point at which this occurs has been considered as a threshold for vitamin D sufficiency. The thresholds found have varied widely and have mainly been based on observational studies. However, to truly establish a threshold for vitamin D effects, this has to be based on randomized controlled trials (RCTs). Methods : 2803 subjects from a general health survey, the Tromsø study, and pooled individual person data from five vitamin D intervention studies (n = 1544) were included. Serum parathyroid hormone (PTH) and change in PTH after vitamin D supplementation was related to serum 25(OH)D levels in steps of 25 nmol/L (<24, 25-49, 50-74, 75-99, >99 nmol/L). Results : In the Tromsø study there was in the females a gradual decrease in serum PTH with increasing serum 25(OH)D with no apparent plateau, whereas in the males the decrease in PTH in subjects with serum 25(OH)D >74 nmol/l was marginal. In pooled RCTs, there was a significant reduction in serum PTH by vitamin D supplementation regardless of baseline serum 25(OH)D level. Conclusions : The use of the serum PTH – 25(OH)D relation from observations studies to determine a threshold for vitamin D sufficiency is highly questionable.